Inositols in PCOS/PMOS: therapeutic role, metabolic implications, and combination with metformin - Biskup, Alicja; Wnęk, Agata; Smagowska, Julia; Staszko, Natalia; Kala-Kaziszyn, Ewa; Bała, Kamila; Stańko, Mikołaj (Quality in Sport, 2026)
Polycystic Ovary Syndrome (PCOS), increasingly referred to as polyendocrine metabolic ovarian syndrome (PMOS), is a heterogeneous endocrine–metabolic disorder associated with reproductive dysfunction, hyperandrogenism, insulin resistance, and increased cardiometabolic risk. Due to the central role of insulin resistance, insulin-sensitizing therapies such as myo-inositol (MI), D-chiro-inositol (DCI), and metformin have gained growing clinical attention. Evidence from studies published between 2015 and 2026 suggests that MI and DCI may improve insulin sensitivity, hormonal balance, and reproductive outcomes, including menstrual cycle regularity and ovulation. The 40:1 MI/DCI ratio remains the most extensively studied formulation and appears to reflect physiological proportions. Metformin continues to play a key therapeutic role, particularly in women with insulin resistance, overweight, or obesity, while combination therapy with inositols may provide additional benefits in selected cases. However, evidence remains heterogeneous, highlighting the need for further high-quality randomized controlled trials to clarify the long-term efficacy and optimal clinical use of inositols in PCOS/PMOS management.